Significados, silencios y olvidos asociados a la experiencia del desplazamiento forzado (2014)
ABSTRACT: In this research the meanings attributed to multiple losses, and the grief movements in displaced persons were analyzed. A qualitative, descriptive study with phenomenological-hermeneutic approach was carried out with the participation of eighteen displaced persons. Categories referred to the changes and losses linked to life before displacement, the exit from the countryside and the arrival into the city were developed. In this article findings dealing with two emerging categories are presented; in the first place, the meanings that affected people attribute to the displacement experience; and, in the second, the silences and oblivions as responses to the violence experienced. Meanings built around displacement allow us to understand the different positions assumed face to face such experience, and the possibilities or difficulties of life reconstruction. Silences and oblivions are particular forms to answer this violence.